Opening the black box: the politics of allocating public resources for health in Barbados - Headley, J (2013)
Within the field of public health, there has been increasing interest in the factors that influence national priorities in health in low- and middle-income countries (LMICs), where resources are often particularly scarce and decision-making processes are often ad- hoc. Understanding how priorities are set in these countries necessitates a look at the process concealed in the black box that transforms policy inputs into outputs. However, rigorous health policy analysis of macro-level priority setting in LMICs is rare. Using a case study approach, this thesis explores the drivers of priority for primary health care, sanitation and HIV/AIDS over the past five decades in Barbados. To do this I use process tracing techniques, drawing on analysis of public expenditure on health from 1960 to 2010, in-depth interviews with key policy actors, non-participant observation, archives, media reports, parliamentary records and other documents. I argue that powerful individual policy actors or 'policy entrepreneurs' act as necessary drivers of macro-level priority setting in Barbados, although they do not single- handedly determine the outcomes. In particular, I find that these actors are successful in generating priority when they are able to propagate powerful framing ideas and can effectively navigate the policy context by seizing windows of opportunity and managing negative constraints. Moreover, because resources are scarce, their ability to mobilize external financial support is also important. In particular, this thesis stresses the fact that allocating public resources for health is a political process and suggests that it is best explained by considering a set of interrelated factors. In doing so, it illustrates the utility of health policy analysis in helping to open the black box of macro-level priority setting in LMICs more broadly.